2007
DOI: 10.1152/jn.00514.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanisms Underlying Antiepileptic Effects of Low- and High-Frequency Electrical Stimulation in Acute Epilepsy in Neocortical Brain Slices In Vitro

Abstract: Schiller Y, Bankirer Y. Cellular mechanisms underlying antiepileptic effects of low-and high-frequency electrical stimulation in acute epilepsy in neocortical brain slices in vitro. J Neurophysiol 97: 1887J Neurophysiol 97: -1902J Neurophysiol 97: , 2007. First published December 6, 2006; doi:10.1152/jn.00514.2006. Approximately 30% of epilepsy patients suffer from drug-resistant epilepsy. Direct electrical stimulation of the epileptogenic zone is a potential new treatment modality for this devastating disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…These inhibitory effects of HFS have been associated with reduction in excitability of neurons, increased inhibitory neurotransmission, and depression of excitatory neurotransmission (Boraud et al, 1996;Durand and Bikson, 2001). In contrast, other HFS studies indicate an increase in neuronal excitation (Schiller and Bankirer, 2007) that desynchronize during prolonged stimulation leading to the illusion of conduction block (Jensen and Durand, 2009). It is possible that a balanced combination of excitation and inhibition may drive the effects of HFS in memory process (McIntyre et al, 2004), an idea that is supported by the enhanced release of both, excitatory and inhibitory amino acids as consequence of HFS.…”
Section: Discussionmentioning
confidence: 96%
“…These inhibitory effects of HFS have been associated with reduction in excitability of neurons, increased inhibitory neurotransmission, and depression of excitatory neurotransmission (Boraud et al, 1996;Durand and Bikson, 2001). In contrast, other HFS studies indicate an increase in neuronal excitation (Schiller and Bankirer, 2007) that desynchronize during prolonged stimulation leading to the illusion of conduction block (Jensen and Durand, 2009). It is possible that a balanced combination of excitation and inhibition may drive the effects of HFS in memory process (McIntyre et al, 2004), an idea that is supported by the enhanced release of both, excitatory and inhibitory amino acids as consequence of HFS.…”
Section: Discussionmentioning
confidence: 96%
“…Since a low stimulation frequency of 0.5 Hz has often been used and seems to be most effective [3,4], this was chosen in the present study. Important aspects are likely to be the degree to which the pathologic activity is localized and how well the treatment is adapted to this [10]. The efficacy is also likely to increase if the treatment is initiated early in the epileptic process; for the separate seizure episode, for the status epilepticus as such, and for the epileptogenesis thereby induced [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, studies have emphasized the effect of electrical stimulation on activity at the cell body, with suppression of somatic activity during stimulation predominating (figure 7a,b;D'Ambrosio et al 1998;Beurrier et al 2001;Bikson et al 2001;Garcia et al 2003;Lee et al 2003;Richardson et al 2003;D'Ambrosio 2004). Recent studies have shown that electrical stimulation also generates changes in axonal activity (Raastad & Shepherd 2003;Soleng et al 2004;Meeks et al 2005;Iremonger et al 2006;De Col et al 2008) including a depression of excitatory synaptic currents (Iremonger et al 2006;Schiller & Bankirer 2007), and conduction blockade in the PNS (Kilgore & Bhadra 2006;Ragnarsson 2007;Tai et al 2007) and in the CNS (figure 7c; Jensen & Durand 2007). Thus, changes in neural activity induced by electrical stimulation provide a means to modulate abnormal communication at several levels within the target network.…”
Section: Role Of Potassium Diffusion In Axon Bundlesmentioning
confidence: 99%